ANALISIS SARANA DAN PRASARANA PADA SEKOLAH LUAR BIASA C TUNAS HARAPAN KARAWANG - Septiyani, Jihan Indah; Hinggil Permana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Facilities and infrastructure play a strategic role in special education because learning services for students with special needs require accessible, adaptive, and functional environments. This study aims to analyze the availability, utilization, constraints, and development efforts of educational facilities and infrastructure at SLB C Tunas Harapan Karawang. The study used a descriptive qualitative approach. The main data were obtained from interview results and were analyzed through data reduction, thematic presentation, and conclusion drawing. The findings show that the available facilities have supported classroom learning and skill-development activities. The school uses existing facilities not only for academic instruction but also for functional learning, independence training, and practical activities. However, several facilities still need further development because special education requires more specific learning spaces, adaptive media, accessibility support, and continuous maintenance than general schools. The school responds to these limitations by optimizing available resources, adjusting learning activities to students' characteristics, and prioritizing practical skill activities. The study concludes that facilities and infrastructure at SLB C Tunas Harapan Karawang have been used productively, but their quality and adequacy should be strengthened through need-based planning, stakeholder collaboration, and periodic evaluation.